2021
DOI: 10.1016/j.celrep.2021.109432
|View full text |Cite
|
Sign up to set email alerts
|

Generation of glucocorticoid-resistant SARS-CoV-2 T cells for adoptive cell therapy

Abstract: Adoptive cell therapy with viral-specific T cells has been successfully used to treat life-threatening viral infections, supporting the application of this approach against COVID-19. We expand SARS-CoV-2 T-cells from the peripheral blood of COVID-19-recovered donors and non-exposed controls using different culture conditions. We observe that the choice of cytokines modulates the expansion, phenotype and hierarchy of antigenic recognition by SARS-CoV-2 T-cells. Culture with IL-2/4/7 but not other cytokine-drive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 48 publications
2
27
0
1
Order By: Relevance
“…Our group successfully expanded SARS-CoV-2-directed cytotoxic T cells (CTL) from the peripheral blood of recovered donors [ 98 ] and is currently leading a phase 1/2 trial to assess the feasibility, safety and efficacy of SARS-CoV-2 virus-specific T cells (VST) in patients with mild to moderate COVID-19 disease (NCT047422595). With increasing evidence supporting the use of corticosteroids to improve outcomes for patients with COVID-19, we furthermore propose a novel engineering strategy delete the gene encoding for the endogenous glucocorticoid receptor ( NR3C1 ) of these donor-derived SARS-CoV-2-specific VSTs using CRISPR/Cas9 gene editing, thereby rendering the lymphocytes resistant to the immunosuppressive potential of corticosteroids [ 98 ].…”
Section: Adoptive Car-nk Immunotherapy For the Treatment Of Viral Pathogens Including Covid-19mentioning
confidence: 99%
“…Our group successfully expanded SARS-CoV-2-directed cytotoxic T cells (CTL) from the peripheral blood of recovered donors [ 98 ] and is currently leading a phase 1/2 trial to assess the feasibility, safety and efficacy of SARS-CoV-2 virus-specific T cells (VST) in patients with mild to moderate COVID-19 disease (NCT047422595). With increasing evidence supporting the use of corticosteroids to improve outcomes for patients with COVID-19, we furthermore propose a novel engineering strategy delete the gene encoding for the endogenous glucocorticoid receptor ( NR3C1 ) of these donor-derived SARS-CoV-2-specific VSTs using CRISPR/Cas9 gene editing, thereby rendering the lymphocytes resistant to the immunosuppressive potential of corticosteroids [ 98 ].…”
Section: Adoptive Car-nk Immunotherapy For the Treatment Of Viral Pathogens Including Covid-19mentioning
confidence: 99%
“…Basar et al showed that corticosteroid resistant T cells targeting SARS-CoV-2 could be generated via CRISPR/Cas9 knockout of the glucocorticoid receptor (NR3C1), and the resulting cells maintain viability and effector function in the presence of dexamethasone in vitro. 90 These and similar approaches may facilitate the use of cell therapy even when immunosuppressive pharmacotherapy must be administered simultaneously.…”
Section: Limitations/ Effect Of Concomitant Steroid Treatment On Adop...mentioning
confidence: 99%
“…Reports have begun to emerge that demonstrate the potential utility of adoptive transfer therapy using ex-vivo expanded SARS-CoV-2 specific T cells [ 37 , 40 , 41 , 42 , 72 , 73 ]. One of the earliest publications in this context utilized a good manufacturing practice (GMP)-compliant methodology to, in vitro, stimulate and expand virus-specific T cells from convalescent donors using SARS-CoV-2 peptides for the purpose of adoptive immunotherapy aimed at immunocompromised patients exposed to SARS-CoV-2 [ 40 ].…”
Section: T Cell Responses In the Setting Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…A subsequent clinical trial demonstrated the safety and feasibility of adoptively transferring purified CD45RA − T cells, which were obtained from SARS-CoV-2 convalescent donors, into partially HLA-matched recipients diagnosed with moderate to severe COVID-19 [ 41 ]. Given that patients with severe COVID-19 are often treated with immune suppressants, ex vivo expanded SARS-CoV-2 specific T cells can be additionally manipulated by CRISPR-Cas9 gene-editing methods to render them resistant to glucocorticoids by inactivating the glucocorticoid receptor gene ( NR3C1 ) [ 42 ]. Evidence of imbalance in the regulatory T cell (Treg)/Th17 cell ratio has also been described in patients that experience respiratory failure in the setting of SARS-CoV-2 infection, hence adoptive immunotherapy approaches that utilize Tregs to mitigate SARS-CoV-2 associated hyper-inflammation are also being explored [ 43 , 44 , 45 , 46 ].…”
Section: T Cell Responses In the Setting Of Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation